International Collaborative Study for the Establishment of the Second International Reference Preparation of Plasmin - Gaffney, P J; Mussett, M V (Thrombosis and Haemostasis, 1983)
An international collaborative study involving seven laboratories was undertaken to assess the suitability of a freeze- dried preparation of human plasmin to replace the current International Reference Preparation (IRP) for plasmin. Chromogenic and fibrinolytic assays were used by all participating laboratories to assess the potencies of the Proposed International Reference Preparation (PIRP) and two other freeze-dried plasmins, one of human and one of porcine originThe data suggest that the PIRP is a more suitable standard for plasmin than the IRP in that the former binds to fibrin whereas only 50% of the latter binds. The PIRP compared well to other plasmin preparations and the potency assays were independent of the assay procedure and substrate used. Degradation studies indicated that the PIRP was far more stable than the glycerol solution of the IRP, surviving for 12 months at 37° C with no significant loss in either amidolytic or fibrinolytic activity. The International Committee for Thrombosis and Haemostasis (Bergamo, 1982) has recommended the use of this material as a standard and it has been established by the Expert Committee on Biological Standardization of the World Health Organization as the second International Reference Preparation for Plasmin with a defined potency of 10 International Units of Plasmin per ampoule.
Keywords: Plasmin; International standard; Fibrinolytic assay; Amidolytic assay